Analisis Penyebab Keterlambatan Pengembalian Buku di Layanan Sirkulasi - Badratun Nafis; Etyana Etyana (Perpustakaan Nasional RI, 2022)
Preliminary. This study aims to find out what is the cause of the delay in returning books at the USK Library. This research is needed as a reference for library evaluation in improving return services and as a form of continuous improvement in library circulation services. The results of this study are expected to minimize delays in returning books by users and improve discipline and quality of library circulation.Research methods. This research is descriptive quantitative, the method used is a survey. The population in this study was the number of users who were late in returning books in 2017 amounted to 6101 people, the number of samples was determined based on the slovin formula of 375 samples, but those who returned intact were 373 questionnaires. The data collection technique used an instrument by distributing a questionnaire containing 5 questions. The data analysis technique in this study uses descriptive analysis method.Results and Discussion. Based on the survey results, the average cause of delays in returning books was because they forgot about 227 respondents (60.9%), the answer choices did not want to return books on time because they still needed the collection as many as 78 people (20.9%). The reason for the three respondents chose other reasons as many as 26 people (7%), the reason was because books were borrowed by friends as many as 21 people (5.6%). Respondents who chose to lose their loan receipts were 13 people (3.5), while those who stated that the collection was lost and had just been found were 5 people (1.3%), users who said they didn't have time to return books were 3 people (0.8%). The average answer that dominates, the user forgets to return the book according to the schedule so that it is late and is subject to fines.Conclusion. The reason why users often return books late is because they forget, in following up on these results, libraries can minimize the causes of delays by utilizing the development of UILIS mobile, by adding notifications before the due date at least one day in advance so that users are more disciplined and not late in returning books.